Features of toll-like receptor genes (TLR-2, TLR-3, TLR-4 and TLR-6) polymorphism in open-angle glaucoma patients - A. V. Shevchenko; V. F. Prokofiev; V. I. Konenkov; V. V. Chernykh; A. N. Trunov (Вавиловский журнал генетики и селекции, 2025)
Modern research shows that innate immunity plays an important role in the pathogenesis of primary open-angle glaucoma (POAG). An increase in the content of toll-like receptors (TLR) in the glaucomatous retina of the human eye was revealed. TLRs can modulate the immune response in glaucoma; provide early recognition of damaging agents, activation of signaling pathways and effector mechanisms of the nonspecific immune defense system aimed at restoring homeostasis. The TLR-encoding genes’ polymorphism alters the amino acid structure of the receptors, which leads to changes in their immune functions: expression level, ligand-binding and coreceptor functions, transport and signal transmission.   The aim was to analyze the association of the TLR2 (rs5743708), TLR3 (rs3775291), TLR4 (rs4986790, rs4986791) and TLR6 (rs5743810) polymorphisms with primary open-angle glaucoma in patients of Western Siberia.   Methods: 99 patients (52 men and 47 women) with a diagnosis of primary open-angle glaucoma were examined. The comparison group consisted of 100 people (81 women and 19 men). TLR2 (rs5743708), TLR3 (rs3775291), TLR4 (rs4986790, rs4986791) and TLR6 (rs5743810) polymorphisms were analyzed by RT-PCR using test systems with Syber Green (Lytex, Russia). Statistical analysis was performed using the software package SPSS 23.0 and Arlequin 3.5.2.2.   Results: the distribution of genotypes in the patient group and in the control group corresponded to the Hardy–Weinberg equilibrium. The genotype frequencies did not significantly differ between the two analyzed groups. The frequency of TLR2-753 ArgArg:TLR6-249 ProPro was increased in the group of patients with POAG. The linkage disequilibrium between two polymorphic positions of the TLR4 gene was revealed. In addition, the linkage disequilibrium between TLR2-TLR6 gene for the glaucoma group and the control group was revealed.   Conclusion: an increase in certain genotypes in the patient group relative to the control group may indirectly indicate the involvement of infectious factors in the initiation of POAG. However, despite the proven importance of the participation of their protein products in the pathogenesis of glaucoma, the relationship of TLR polymorphism requires additional research taking into account the ethnic characteristics of patients and intergenic interactions for a better understanding of the complex mechanisms of disease development. This will help carry out early diagnosis and develop the necessary therapeutic strategy.